2012
DOI: 10.1007/s00442-012-2317-9
|View full text |Cite
|
Sign up to set email alerts
|

Physiology of the seasonal relationship between the photochemical reflectance index and photosynthetic light use efficiency

Abstract: The photochemical reflectance index (PRI) is regarded as a promising proxy to track the dynamics of photosynthetic light use efficiency (LUE) via remote sensing. The implementation of this approach requires the relationship between PRI and LUE to scale not only in space but also in time. The short-term relationship between PRI and LUE is well known and is based on the regulative process of non-photochemical quenching (NPQ), but at the seasonal timescale the mechanisms behind the relationship remain unclear. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
127
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(146 citation statements)
references
References 53 publications
11
127
2
1
Order By: Relevance
“…NDCI was also strongly seasonally correlated with A ( Figure S4a), and SIPI was weakly and negatively correlated with A ( Figure S4b), but neither was as strongly correlated as PRI. PRI was not only sensitive to long-term carotenoid/chlorophyll changes, but also to short-term xanthophyll pigment conversion [46,50,66]. The strong correlations of PRI with NDCI and SIPI ( Figure S5) supported the importance of pigments in using PRI to monitor the photosynthetic apparatus at seasonal timescales [46], because NDCI is an index of chlorophyll changes [51,61] and SIPI is associated with carotenoid and chlorophyll ratios [62].…”
Section: Pri Assessment Of Seasonal Photosynthesis Under Long-term Drmentioning
confidence: 97%
“…NDCI was also strongly seasonally correlated with A ( Figure S4a), and SIPI was weakly and negatively correlated with A ( Figure S4b), but neither was as strongly correlated as PRI. PRI was not only sensitive to long-term carotenoid/chlorophyll changes, but also to short-term xanthophyll pigment conversion [46,50,66]. The strong correlations of PRI with NDCI and SIPI ( Figure S5) supported the importance of pigments in using PRI to monitor the photosynthetic apparatus at seasonal timescales [46], because NDCI is an index of chlorophyll changes [51,61] and SIPI is associated with carotenoid and chlorophyll ratios [62].…”
Section: Pri Assessment Of Seasonal Photosynthesis Under Long-term Drmentioning
confidence: 97%
“…In contrast, very long-term stress can change the content of chlorophyll and the pool size of the xanthophyll cycle pigments. It is known that similar changes can also influence PRI [48,122].…”
Section: Conditions Of Measurementmentioning
confidence: 99%
“…Connections between PRI and other photosynthetic parameters, including a quantum yield of photosystem II (∆F/F m ') [38,41,42,[45][46][47][48][49], photosynthetic light use efficiency (LUE) [3,48,[50][51][52][53][54][55], and net CO 2 uptake [47,[56][57][58][59], are actively being investigated. However, the results of these different works vary considerably, e.g., the linear correlation coefficients between PRI and NPQ can range from −0.90 [38,49,60] to +0.86 [41] in different investigations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Xanthophyll cycle pigments provide a means of dissipating excess energy when light absorbed by plants exceeds the photosynthetic capacity to avoid damage to the photosynthetic system, which influences the PRI signal on a diurnal timescale. It was later demonstrated by Porcar-Castell et al [19] that on seasonal scales the main physiological mechanism controlling the relationship between PRI and LUE is not the xanthophyll cycle, but rather dynamics in the relative pigments pools of chlorophyll and carotenoids. This was further confirmed by Gamon et al [20] and Wong and Gamon [14], who observed high correlations between PRI responses and adjustments in chlorophyll:carotenoid ratios.…”
Section: Introductionmentioning
confidence: 99%